2007
DOI: 10.1097/blo.0b013e31805d85e4
|View full text |Cite
|
Sign up to set email alerts
|

Joint Salvage for Pathologic Fracture of Giant Cell Tumor of the Lower Extremity

Abstract: Pathologic fracture through giant cell tumor is thought to be associated with higher rates of recurrence and poor functional outcome. We compared patients with and without pathologic fracture through giant cell tumor of weightbearing long bones. We retrospectively reviewed 139 patients with giant cell tumor of weightbearing long bones with (n = 43) and without (n = 96) pathologic fracture at presentation; the two groups had similar demographics. Joint salvage was successful in 84% of the fracture group and 96%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 36 publications
4
59
2
Order By: Relevance
“…However, to our knowledge, there is no clear definition of "more," "extensive" or "severe" destruction" in grade III GCTs and the reported indications of wide resection for GCT are also heterogeneous [5,7,22,23,30,38]. Furthermore, another dilemma of the application of the system of Campanacci et al is that some authors declared that conservative treatments instead of wide resection should be recommended for grade III GCTs [44,45]. Therefore, the role of the classifications of Enneking and Campanacci et al in planning the initial surgical treatment is limited.…”
Section: The Clinicoradiological System Of Gctmentioning
confidence: 80%
See 3 more Smart Citations
“…However, to our knowledge, there is no clear definition of "more," "extensive" or "severe" destruction" in grade III GCTs and the reported indications of wide resection for GCT are also heterogeneous [5,7,22,23,30,38]. Furthermore, another dilemma of the application of the system of Campanacci et al is that some authors declared that conservative treatments instead of wide resection should be recommended for grade III GCTs [44,45]. Therefore, the role of the classifications of Enneking and Campanacci et al in planning the initial surgical treatment is limited.…”
Section: The Clinicoradiological System Of Gctmentioning
confidence: 80%
“…There are limited data in the literature comparing local recurrence rates between patients with and without pathological fracture [4,7,8]. Deheshi et al [45] found no difference in local recurrence after curettage between patients with or without pathological fracture. However, in a Canadian multicentre study by Turcotte et al involving 186 patients, displaced fracture was shown to be a prognostic factor for local recurrence [28].…”
Section: Pathological Fracturementioning
confidence: 97%
See 2 more Smart Citations
“…Deheshi et al [91] indicate that there is no difference in terms of recurrence after curettage in patients with or without a pathological fracture. Dreinhöfer et al [92] also believe that pathological fracture is not a contraindication for curettage and PMMA.…”
Section: Treatment After Pathological Fracturementioning
confidence: 99%